2022
DOI: 10.3390/ma15072615
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical Properties of Biochar Produced from Goldenrod Plants

Abstract: Torrefaction is one of the methods of thermal treatment of biomass, which allows obtaining a product of better quality in the form of biochar. The aim of the paper was to analyze the possibility of using goldenrod (Solidago canadensis, Solidago gigantea) for the production of biochar. The torrefaction process involved the vegetative and generative parts as well as the whole plant at temperatures of 250 °C and 275 °C, for 3 h. Next, the physicochemical properties of the raw material and biochar were determined,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 56 publications
1
0
0
Order By: Relevance
“…This observation is consistent with the work of Tu et al 70 The moisture content of the biochars decreased from 10.68 for the original biomass to 9.12 and 9.15 wt% for biochar and magnetic biochar, respectively. This is in agreement with the work of Tsai et al , 62 Liu et al , 67 Shariff et al 71 and Łapczyńska-Kordon et al 72 The ash content of the biochar increased from 12.50 to 18.26 wt% when compared with the feedstock, this is due to the mineral content of ash, which remains in biochar after the pyrolysis process, while organic matter is lost. Moreover, the surface loaded iron oxide significantly increased the ash content.…”
Section: Resultssupporting
confidence: 92%
“…This observation is consistent with the work of Tu et al 70 The moisture content of the biochars decreased from 10.68 for the original biomass to 9.12 and 9.15 wt% for biochar and magnetic biochar, respectively. This is in agreement with the work of Tsai et al , 62 Liu et al , 67 Shariff et al 71 and Łapczyńska-Kordon et al 72 The ash content of the biochar increased from 12.50 to 18.26 wt% when compared with the feedstock, this is due to the mineral content of ash, which remains in biochar after the pyrolysis process, while organic matter is lost. Moreover, the surface loaded iron oxide significantly increased the ash content.…”
Section: Resultssupporting
confidence: 92%
“…Bedmutha et al (2011) and Nanda et al (2016) also reported that pyrolysis at higher temperatures leads to greater cracking of organic components, thereby reducing biochar production. The ash content was higher in corn straw than in peanut shells, and biochar ash content was related to raw materials (Łapczyńska-Kordon et al 2022).…”
Section: Resultsmentioning
confidence: 95%
“…S. canadensis biomass contains high lignin contents (28.68%), which leads to a high heating value of 19.894 MJ kg −1 . Recent studies have shown that vegetative and generative parts of S. canadensis can be used as raw material in biochar production [106]. The observed results have shown a significant impact of the plant species and the sampled parts on the ash content, volatile matter content, calorific value, and heat of combustion.…”
Section: Fuelmentioning
confidence: 94%
“…Diterpenes, also common in Solidago, can act as insect antifeedants and growth inhibitors [105]. Given the acceptable ash content level, biochar derived from S. canadensis can be used in agriculture for enhancing soil water retention capacity, greenhouse cultivation, composting organic materials, and mitigating unpleasant odours [106]. As a result of torrefaction, one of the main steps when making biochar, the ash content in biochar from the S. canadensis increased to 20%.…”
Section: Agriculture and Food Processingmentioning
confidence: 99%